2006
DOI: 10.1038/sj.bjp.0706662
|View full text |Cite
|
Sign up to set email alerts
|

Red wine alcohol promotes quercetin absorption and directs its metabolism towards isorhamnetin and tamarixetin in rat intestine in vitro

Abstract: 1 Moderate consumption of red wine has been associated with beneficial effects on human health, and this has been attributed to the flavonoid content. Factors that influence the bioavailability of this group of polyphenolic compounds are therefore important. 2 Using the rat cannulated everted jejunal sac technique, we have investigated the effect of alcohol on the intestinal absorption of quercetin and its 3-O-glucoside from red wine. Tissue preparations were incubated in whole or dealcoholised red wine, dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…In 2005, Kern et al [80] reported a perspective on the antiproliferative effect and demonstrated the potent EGFRinhibitory properties of polyphenolrich apple juice extract in adenocarcinoma colon in vitro model (HT29) [80] . Another study suggested that the beneficial effects of red wine on human health were attributable to the flavonoid content, which channeled the body metabolism towards Omethylation to yield compounds with potential protective effects against cancer [81] .…”
Section: Colon Cancermentioning
confidence: 99%
“…In 2005, Kern et al [80] reported a perspective on the antiproliferative effect and demonstrated the potent EGFRinhibitory properties of polyphenolrich apple juice extract in adenocarcinoma colon in vitro model (HT29) [80] . Another study suggested that the beneficial effects of red wine on human health were attributable to the flavonoid content, which channeled the body metabolism towards Omethylation to yield compounds with potential protective effects against cancer [81] .…”
Section: Colon Cancermentioning
confidence: 99%
“…The authors suggested that resveratrol metabolite concentrations were statistically higher after the DRW compared with RW intervention (P ¼ 0.002). However, it seems clear from a great number of recent studies that the cardiovascular effects of polyphenols are dependent on their bioavailability, and alcohol in RW may improve polyphenol availability by increasing its intestinal absorption or by delaying its excretion (2,3), indicating that RW intake should produce higher concentrations of urinary resveratrol metabolites than DRW ingestion. It is, therefore, reasonable to assume that the consumption of RW and DRW also should, at least, lead to similar concentrations of urinary resveratrol metabolites, despite the fact that the resveratrol content of RW is slightly higher than that of DRW as depicted in Table 1 of their article.…”
Section: Absorption and Metabolism Of Red Wine Polyphenols And Their mentioning
confidence: 99%
“…[1][2][3] Consequently, many physiological functions of flavonoids, such as their preventive effects on cancer, cardiovascular disease, liver injury and oxidative stress, neuroprotective effects, and hypoglycemic effects, have been investigated and reported, [4][5][6][7][8][9][10][11] and the bioavailability, absorption from the gastro-intestinal tract, and metabolism of flavonoids have been examined in relation to their function. [12][13][14] However, few reports have been presented on the precise relationship between the chemical structure of dietary flavonoids and their bioavailability or functions. Therefore, it is very important to determine the relationship between the chemical structures and physiological functions in order to know which structures are more important for preventing disease.…”
mentioning
confidence: 99%